Review of current nuclear fallout codes. (May 2017) - Auxier, Jerrad P.; Auxier, John D.; Hall, Howard L.
Abstract: The importance of developing a robust nuclear forensics program to combat the illicit use of nuclear material that may be used as an improvised nuclear device is widely accepted. In order to decrease the threat to public safety and improve governmental response, government agencies have developed fallout-analysis codes to predict the fallout particle size, dose, and dispersion and dispersion following a detonation. This paper will review the different codes that have been developed for predicting fallout from both chemical and nuclear weapons. This will decrease the response time required for the government to respond to the event. Highlights: A comparison of nuclear fallout codes using the MOE and NAD values. Compared HPAC, DELFIC, FDC, and HYSPILT to known nuclear fallout data. Compared NARAC and HPAC to stable, neutral and unstable gas dispersion to determine fallout accuracy.